Body image satisfaction and weight concerns among a Mediterranean adult population. (December 2017) - Bibiloni, Maria del Mar; Coll, Josep; Pich, Jordi; Pons, Antoni; Tur, Josep
Abstract Background People tend to underestimate their current weight and overestimate their height minimizing health risk factors. The aim of this study was to assess body weight satisfaction, acceptance of body image, weight concern and dieting habits among a Mediterranean adult population. Methods Cross-sectional survey was carried out (2009–2010) in the Balearic Islands, Spain. A random sample (n  = 1081) of young (18–35 y.o.) and middle-aged adults (36–55 y.o.) was interviewed and anthropometrically measured. Results Women were more dissatisfied being overweight, less dissatisfied being underweight, and more worried about weight gain than men. Middle-aged participants were more dissatisfied with body shape and underestimated body weight than young's. Employed women defined better current weight than unemployed, but unemployed were more worried about body weight gain. Overweight adults were more likely to underestimate their body weight but were also very worried about weight gain and more likely to report current dieting than their leaner counterparts. Active participants self-reported better body weight and were more satisfied with body image than sedentary. Conclusions Most of studied population reported body image dissatisfaction, but half of them are not worried about it. Women were more concerned about their body weight status. Practice of physical activity is a positive factor in self-perception. Holistic strategies are needed to avoid promoting unreal bodies, as well as the acceptance of the real body image.